2018
DOI: 10.1007/s40572-018-0179-y
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Epidemiologic Studies on Greenness and Health: Updated Literature Through 2017

Abstract: Purpose of review Many studies suggest that exposure to natural vegetation, or greenness, may be beneficial for a variety of health outcomes. We summarize the recent research in this area. Recent findings We observed consistent and strong evidence of associations for higher greenness with improvements in birth weights and physical activity, as well as lower mortality rates. Recent studies also suggested that exposure to greenness may lower levels of depression and depressive symptoms. The evidence on greenne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
316
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(336 citation statements)
references
References 66 publications
12
316
3
5
Order By: Relevance
“…These preliminary findings support previous research findings suggesting that quality of green exposure can play a more important role than the quantity or accessibility of UGS for the MH&WB outcomes [29,42] and build on the previous research by providing evidence for an objective improvement in brain pattern activity typically associated with positive mood/affect. Nevertheless, this is the first study to demonstrate that in-situ exposure to a contemplative space can elicit FAA.…”
Section: Discussionsupporting
confidence: 88%
“…These preliminary findings support previous research findings suggesting that quality of green exposure can play a more important role than the quantity or accessibility of UGS for the MH&WB outcomes [29,42] and build on the previous research by providing evidence for an objective improvement in brain pattern activity typically associated with positive mood/affect. Nevertheless, this is the first study to demonstrate that in-situ exposure to a contemplative space can elicit FAA.…”
Section: Discussionsupporting
confidence: 88%
“…New Evidence In the context of asthma, studies suggest that greenspace could increase exposure to microbial antigens that may impact immune system development, counteract environmental pollution of urban communities, and mediate family relationship stress [82][83][84]. Despite these hypotheses, there are inconsistent associations with greenspace and asthma [85][86][87]. Two meta-analyses demonstrated a non-significant trend toward reduced asthma incidence in areas with higher greenspace, though they are limited by heterogeneity [85,87].…”
Section: Intermediary Determinantsmentioning
confidence: 99%
“…13,14 Efforts to promote the biophilic design in practice include identifying design attributes and categorizing them into three domains (ie, nature in the spaces, natural analogues, and nature of the space) and 14 patterns, prioritizing the most prominent nature-health relationships in the built environment. [16][17][18][19][20] Less is known about possible health and well-being benefits of encountering nature indoors. [16][17][18][19][20] Less is known about possible health and well-being benefits of encountering nature indoors.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 A significant body of existing research has shown the health benefits derive from contact with or emersion in nature occurring outdoors. [16][17][18][19][20] Less is known about possible health and well-being benefits of encountering nature indoors. 21 What evidence exists is mainly focused on the benefits of "nature in the space," including natural views from window, indoor plants, and natural light.…”
Section: Introductionmentioning
confidence: 99%